Os Corpos da Devi: religião e género em diáspora - Lourenço, Inês (2011)
This thesis focuses on the Gujarati Hindu diaspora in Portugal, and particularly on the key role played by women in the construction of gender and religious identities, therefore contributing to the cultural reproduction of their community. Based on a longterm fieldwork carried out amongst the Hindu community of Santo António dos Cavaleiros (Loures), I aim at showing the way that Hindu women in Portugal are ascribed new status through religion, as the perpetuators of what is perceived as traditional knowledge, consequently replacing the role played by male pujari in the negotiation of cultural and religious belonging. By the same token, these women guarantee the upholding of a patriarchal ideology within transnational networks framed by a conservative ideology. The ritual centrality given to women by the Gujarati diaspora in Portugal results from its specific features, namely its weak economical structure inhibiting a lasting and regular attendance of Hindu priests, and the lack of professional occupations held by a significant number of these women. In this as in other Hindu diasporas in the world, India works out as the structural reference upon which the diasporic identity is asserted.